2011
DOI: 10.1098/rsbl.2011.0794
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to conspecific chemicals suppresses cane toad growth and survival

Abstract: Adaptations to suppress the viability of conspecifics may provide novel ways to control invasive taxa. The spread of cane toads (Rhinella marina) through tropical Australia has had severe ecological impacts, stimulating a search for biocontrol. Our experiments show that cane toad tadpoles produce waterborne chemical cues that suppress the viability of conspecifics encountering those cues during embryonic development. Brief (72 h) exposure to these cues in the egg and posthatching phases massively reduced rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 35 publications
2
52
1
1
Order By: Relevance
“…Smaller body size also renders a young cane toad more vulnerable to desiccation [51], [52], predation by carnivorous ants [55], cannibalism [54], and mortality after lungworm infection [53]. Thus, for this species, we can confidently conclude that (a) toad body size at metamorphosis can be reduced by multiple biotic and abiotic characteristics of the larval environment [43], [44], [45], [46], (b) that any reduction in body size at metamorphosis is likely to impose subsequent fitness costs, and (c) the strength of any link between metamorph mass and subsequent survival and growth rates will vary through time and space, at least partly because of variation in the availability of environmental resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller body size also renders a young cane toad more vulnerable to desiccation [51], [52], predation by carnivorous ants [55], cannibalism [54], and mortality after lungworm infection [53]. Thus, for this species, we can confidently conclude that (a) toad body size at metamorphosis can be reduced by multiple biotic and abiotic characteristics of the larval environment [43], [44], [45], [46], (b) that any reduction in body size at metamorphosis is likely to impose subsequent fitness costs, and (c) the strength of any link between metamorph mass and subsequent survival and growth rates will vary through time and space, at least partly because of variation in the availability of environmental resources.…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by increasing larval competition with conspecifics (through concentrating oviposition in a smaller number of sites, thus increasing larval density: [42]), or heterospecifics (by encouraging other taxa of anurans to oviposit in the same ponds as used by the target species: [43], [44]. Alternatively, we could use pheromonal cues (from conspecifics, heterospecific anurans, or predators) to induce reaction norms that result in reduced size at metamorphosis [45], [46]. Such manipulations rely upon the assumption that reducing mean body size at metamorphosis will reduce subsequent recruitment of that cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical addition to water bodies may represent a future technique for suppressing the number and sizes of cane toads developing to the tadpole and adult stages (Crossland and Shine 2012). Recent research by Crossland and Shine (2012) has shown that cane toad eggs placed in water that already had a cohort of conspeci c tadpoles had 45% greater mortality and 40% smaller tadpole body sizes than tadpoles grown in fresh water.…”
Section: Historic and Current Managementmentioning
confidence: 99%
“…Recent research by Crossland and Shine (2012) has shown that cane toad eggs placed in water that already had a cohort of conspeci c tadpoles had 45% greater mortality and 40% smaller tadpole body sizes than tadpoles grown in fresh water. Therefore, cane toad tadpoles produce waterborne chemical cues that suppress conspeci c embroyic development (Crossland and Shine 2012).…”
Section: Historic and Current Managementmentioning
confidence: 99%
See 1 more Smart Citation